Access and use of electronic media in financial institutions in Ecuador [Acceso y uso de medios electronicos en las entidades financieras en Ecuador] - Espinoza Loayza, V. (2016)
The internet has revolutionized the way of doing business. The financial system has not been the exception; customers are becoming more familiar with the advances and technological developments. This is a great opportunity to increase market share, improve internal and external communication flows, influencing the optimizing of the results and thereby achieve greater benefits in economic terms and social reputation. Digital network stands as a key ally of the financial institutions to achieve a better position in their respective markets. Online banking offers opportunities and challenges; however, to make it profitable it is necessary that its target audience has minimum levels of financial and technological education in order to be able to efficiently leverage all the advantages of this mode of Banking. This article discusses the results of an investigation that adopted as a general framework the financial system of Ecuador. As well, was to review electronic mechanisms access that financial institutions have, and how their clients use them. By offering there is a variety in the access channels, customers still experiencing resistance in its intensive use; factors such as insecurity and ignorance are the main causes of this behavior.